(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
The administration of medical records entails multifaceted legal and ethical responsibilities aimed at protecting patient rights, ensuring data accuracy, and facilitating appropriate accessibility. This article delves into the intricate landscape of medical record management, exploring key considerations such as patient confidentiality, data accessibility, and accuracy. It navigates through the regulatory framework, including HIPAA regulations, while addressing the ethical dilemmas faced by healthcare providers. Furthermore, it discusses strategies for maintaining the delicate balance between safeguarding patient privacy and promoting data accessibility for quality healthcare delivery. By examining real-world challenges and offering insights into best practices, this article serves as a comprehensive guide for healthcare professionals navigating the legal and ethical complexities of medical record administration.